Hydrophilically modified composite gas separation membranes, methods of making and using the same
Patent Information
- Application Number
- CN202510559757.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-29
- Publication Date
- 2026-10-30
AI Technical Summary
[0005]本发明的目的是为了克服现有技术的气体分离膜存在的气体渗透性差且工业化难度大的问题,提供一种亲水改性复合气体分离膜及其制备方法与应用,该气体分离膜中包含由具有特定结构的亲水聚合物形成的亲水聚合物层,在改善气体分离膜表面的亲水性的同时,降低了气体分离膜的缺陷,改性后膜还保持较高的气体渗透性
[0015]本发明中,所述亲水复合气体分离膜中包含由具有特定结构的亲水聚合物形成的亲水聚合物层,该亲水聚合物中含有来自含醚键的多元胺的结构单元,能够在改善气体分离膜表面的亲水性的同时,降低了气体分离膜的缺陷,提高了气体分离膜对气体的渗透性。
Smart Images

Figure CN122999005A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of polymer membrane materials and membrane separation technology, specifically to a hydrophilic modified composite gas separation membrane, its preparation method, and its application. Background Technology
[0002] Gas separation membrane technology utilizes the difference in permeation rates of different gas molecules through a membrane to achieve the separation and purification of different gas components. Permeation rate and selectivity are important indicators for evaluating the performance of gas separation membranes. Multilayer composite membranes consist of an ultrathin separation layer, an intermediate layer, and a porous support. The porous support possesses good mechanical properties, the dense, ultrathin separation layer provides the primary separation function, and the intermediate layer typically serves to suppress the permeation of the separation layer membrane material within the porous support and improve interlayer interfacial compatibility. Different layers of the multilayer composite membrane provide different functions, and the structure of each layer can be controlled and optimized by using different membrane materials, resulting in composite membranes with both high permeability and high selectivity. The layers of the gas separation composite membrane in this technical field can be prepared using various methods, including phase inversion, coating, and interfacial polymerization.
[0003] Polydimethylsiloxane (PDMS) is a commonly used interlayer membrane material, possessing flexible polymer segments and high gas permeability. Silane materials are low surface energy substances with hydrophobic surfaces, making it difficult for the polar solvents required for the separation layer membrane fabrication process to spread well on the PDMS surface. To improve the hydrophilicity of the PDMS layer, researchers both domestically and internationally have utilized various methods, including plasma technology, the introduction of hydrophilic side chains, and surface modification with tannins and dopamine, to achieve hydrophilic modification of the PDMS surface. Firstly, several studies both domestically and internationally have successfully achieved hydrophilic modification of PDMS using plasma technology. High-throughput composite membranes were prepared using pebax1657 ethanol-water solution after hydrophilic modification of the PDMS layer using oxygen plasma technology. To facilitate further industrial scale-up, researchers also used the more economical air plasma technology to hydrophilic modify both the PDMS layer and the PEO-blocked PDMS layer, preparing high-throughput pebax1657 composite membranes. Secondly, a hydrophilic PDMS layer was prepared using an amino-modified silane solution, and a multilayer composite film was prepared by coating it with a Pebax solution. Finally, the researchers also modified the surface of PDMS with tannic acid and dopamine to achieve good spreading of the polymer polar solution in the modified PDMS layer.
[0004] Current publicly available technologies for hydrophilic modification of PDMS face challenges such as expensive and complex equipment, long modification processes, significant gas flux loss, and difficulty in industrial scale-up. Reports on plasma-modified PDMS mention the need for vacuum conditions during the experimental phase, which is difficult to achieve in continuous industrial production due to the high equipment cost. Furthermore, the hydrophilicity of the PDMS surface after plasma modification only lasts for a limited time, requiring immediate coating with a separation layer solution. CN115608177A also indicates that plasma treatment of the PDMS layer results in a dense SiOx layer, significantly reducing gas flux. While hydrophilic PDMS layers can be prepared using amino-containing silane solutions, the permeability of the hydrophilic PDMS is significantly reduced, with a CO2 permeation rate of 1900-2500 and a CO2 / N2 selectivity of approximately 9. Additionally, the modification of PDMS with tannic acid and dopamine typically requires soaking in the solution for tens of minutes or even hours, and a shaker is generally needed to enhance coating uniformity and reduce reaction time. Summary of the Invention
[0005] The purpose of this invention is to overcome the problems of poor gas permeability and difficulty in industrialization of existing gas separation membranes, and to provide a hydrophilic modified composite gas separation membrane, its preparation method and application. The gas separation membrane contains a hydrophilic polymer layer formed by a hydrophilic polymer with a specific structure, which improves the hydrophilicity of the gas separation membrane surface, reduces the defects of the gas separation membrane, and the modified membrane also maintains high gas permeability.
[0006] To achieve the above objectives, the first aspect of the present invention provides a hydrophilic modified composite gas separation membrane, wherein the gas separation membrane comprises, in sequence, a porous support layer, a hydrophobic polymer layer, and a hydrophilic polymer layer;
[0007] The hydrophilic polymer forming the hydrophilic polymer layer includes structural unit I from polyacrylamide chloride, structural unit II from polyamine containing ether bonds, and structural unit III optionally from hydroxyl compound;
[0008] In this structure, structural unit I and structural unit II are connected by amide bonds, and structural unit I and structural unit III are connected by ester groups.
[0009] A second aspect of the present invention provides a method for preparing a hydrophilic modified composite gas separation membrane, wherein the method comprises:
[0010] (1) A hydrophobic polymer layer is prepared on a porous support layer to obtain a composite membrane;
[0011] (2) After the composite membrane is first contacted with an organic phase containing polyacryl chloride and dried, it is then second contacted with an aqueous phase containing a polyamine containing an ether bond, optionally a hydroxyl compound, an acid absorbent and optionally a surfactant, and then heat-treated to obtain the hydrophilic modified composite gas separation membrane.
[0012] A third aspect of the present invention provides a hydrophilic modified composite gas separation membrane prepared by the above method.
[0013] A fourth aspect of the present invention provides an application of the above-mentioned hydrophilic modified composite gas separation membrane in the separation of gas mixtures.
[0014] Through the above technical solutions, the hydrophilic modified composite gas separation membrane, its preparation method, and its application provided by the present invention achieve the following beneficial effects:
[0015] In this invention, the hydrophilic composite gas separation membrane includes a hydrophilic polymer layer formed by a hydrophilic polymer with a specific structure. The hydrophilic polymer contains structural units from polyamines containing ether bonds, which can improve the hydrophilicity of the gas separation membrane surface, reduce defects in the gas separation membrane, and improve the permeability of the gas separation membrane to gas.
[0016] In the preparation method of the hydrophilic composite gas separation membrane provided by the present invention, an interfacial polymerization process is used to prepare a hydrophilic polymer layer on a hydrophobic polymer layer by placing polyacrylamide chloride, polyamine containing ether bonds, and optionally a hydroxyl-containing compound. This not only improves the compatibility between the layers of the gas composite membrane, but also improves the hydrophilicity of the gas separation membrane. The modified layer has a small thickness and low gas transmission resistance, and the modified composite membrane still has high gas permeability.
[0017] Furthermore, compared to traditional hydrophilic modification techniques, the method for preparing the hydrophilic modified composite gas separation membrane provided by this invention utilizes interfacial polymerization to achieve hydrophilic modification of the hydrophobic polymer layer. This preparation method features simple equipment, easy operation, good technical and economic efficiency, and ease of industrial application. Attached Figure Description
[0018] Figure 1 The images show the surface (left) and cross-sectional electron microscope (EM) images (right) of the membrane after interfacial polymerization modification in Example 1.
[0019] Figure 2 These are the infrared spectra of the films prepared in Example 1 and Comparative Example 1.
[0020] Figure 3 These are the XPS spectra of the films prepared in Example 1 and Comparative Example 1. Detailed Implementation
[0021] The endpoints and any values of the ranges disclosed herein are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of the various ranges, the endpoint values of the various ranges and individual point values, and individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed herein.
[0022] The first aspect of the present invention provides a hydrophilic modified composite gas separation membrane, wherein the gas separation membrane comprises, in sequence, a porous support layer, a hydrophobic polymer layer and a hydrophilic polymer layer;
[0023] The hydrophilic polymer forming the hydrophilic polymer layer includes structural unit I from polyacrylamide chloride, structural unit II from polyamine containing ether bonds, and optionally structural unit III from hydroxyl-containing compounds;
[0024] In this structure, structural unit I and structural unit II are connected by amide bonds, and structural unit I and structural unit III are connected by ester groups.
[0025] In this invention, the hydrophilic modified composite gas separation membrane includes a hydrophilic polymer layer formed by a hydrophilic polymer with a specific structure. The hydrophilic polymer contains structural units from polyamines containing ether bonds, which can improve the hydrophilicity of the gas separation membrane surface while reducing the transmission resistance of the gas separation membrane, so that the gas separation membrane maintains high gas permeability.
[0026] In this invention, structural units I and III, which are connected by ester groups, form flexible polyester segments in the hydrophilic polymer, while structural units I and II, which are connected by amide bonds, form polyamide segments.
[0027] In this invention, the hydrophilic polymer is formed by linking structural units II from ether-containing polyamines and, optionally, structural units III from hydroxyl-containing compounds through structural unit I from polyacrylamide to form a random copolymer.
[0028] In this invention, the content of carbon atoms in the surface of the hydrophilic modified composite gas separation membrane was measured by XPS to be 50-75 at%, nitrogen atoms 2-8 at%, oxygen atoms 20-27 at%, and silicon atoms 0-16 at%. In particular, when the silicon atom content is less than 10 at%, the hydrophilic modified composite layer has better hydrophilicity.
[0029] According to the present invention, the polyacryl chloride is selected from at least one of oxaloyl chloride, adipicoyl chloride, cyclohexanoyl chloride, terephthaloyl chloride, isophthaloyl chloride and trimesoyl chloride, preferably selected from isophthaloyl chloride and / or trimesoyl chloride.
[0030] According to the present invention, the polyamine containing ether bonds is selected from at least one of polyoxyethylene diamine, ethylene glycol bis(3-aminopropyl) ether, polyetheramine and diethylene glycol bis(3-aminopropyl) ether.
[0031] According to the present invention, the hydroxyl-containing compound is selected from at least one of polyvinyl alcohol, (2-hydroxypropyl)-α-cyclodextrin, (2-hydroxypropyl)-β-cyclodextrin and water-soluble polymeric cyclodextrin.
[0032] In this invention, polyacyl chlorides, polyamines containing ether bonds, and hydroxyl-containing compounds are polymerized at the interface onto the surface of a hydrophobic polymer layer to form a hydrophilic polymer layer.
[0033] In a preferred embodiment of the present invention, in order to reduce the gas transmission resistance of the interfacial polymerization modified layer, a cyclodextrin compound containing a 3D cavity is introduced into the hydrophilic polymer layer, which can further improve the permeability of the hydrophilic polymer layer. The cyclodextrin compound containing a 3D cavity is selected from at least one of (2-hydroxypropyl)-α-cyclodextrin, (2-hydroxypropyl)-β-cyclodextrin and water-soluble polymeric cyclodextrin.
[0034] According to the present invention, the polymer forming the hydrophobic polymer layer is selected from at least one of poly(1-trimethsilyl-1-propyne), polydimethylsiloxane, and polydimethylsiloxane-polyoxyethylene copolymer.
[0035] In this invention, the type of porous support layer is not particularly limited, and it can be made of various existing membrane materials with certain strength that can be used for ultrafiltration and microfiltration. Preferably, the porous support layer comprises a bottom layer and a porous layer in sequence. The bottom layer is a non-woven fabric material, preferably polyester and / or polyolefin. The porous layer can be made of at least one of polyvinylidene fluoride, polypropylene, cellulose acetate, polyethylene, polytetrafluoroethylene, polyetherimide, polyimide, polyacrylonitrile, polyethersulfone, and polysulfone.
[0036] In this invention, there is no particular limitation on the source of the porous support layer. It can be commercially available, or the porous layer can be prepared at the bottom layer according to conventional preparation methods in the art, such as phase transformation method, to obtain the porous support layer.
[0037] According to the present invention, the contact angle of the gas separation membrane is 50-85°.
[0038] In this invention, when the contact angle of the gas separation membrane meets the above-mentioned range, it indicates that the surface of the gas separation membrane containing the hydrophilic polymer layer is hydrophilic and can be used for the spreading and wetting of hydrophilic solvents.
[0039] Furthermore, the contact angle of the gas separation membrane is 65-80°.
[0040] In this invention, there are no special requirements for the thickness of the porous support layer. For example, the thickness of the porous support layer is 20-200 μm.
[0041] According to the present invention, the thickness of the hydrophobic polymer layer is 50-300 nm.
[0042] According to the present invention, the thickness of the hydrophilic polymer layer is 50-500 nm.
[0043] In this invention, when the hydrophobic polymer layer and / or hydrophilic polymer layer in the gas separation membrane each independently satisfy the above-mentioned range, the composite membrane surface can be hydrophilic while maintaining high gas permeability.
[0044] Furthermore, the thickness of the hydrophobic polymer layer is 80-150 nm.
[0045] Furthermore, the thickness of the hydrophilic polymer layer is 90-200 nm.
[0046] A second aspect of the present invention provides a method for preparing a hydrophilic composite gas separation membrane, wherein the method includes:
[0047] (1) A hydrophobic polymer layer is prepared on a porous support layer to obtain a composite membrane;
[0048] (2) After the composite membrane is first contacted with an organic phase containing polyacryl chloride and dried, it is then second contacted with an aqueous phase containing a polyamine containing an ether bond, optionally a hydroxyl compound, an acid absorbent and optionally a surfactant, and optionally subjected to heat treatment to obtain the hydrophilic composite gas separation membrane.
[0049] In this invention, an interfacial polymerization process is used to prepare a hydrophilic polymer layer on a hydrophobic polymer layer by placing polyacrylamide chloride, polyamine containing ether bonds, and optionally hydroxyl-containing compounds on a hydrophobic polymer layer. This not only improves the compatibility between the layers of the gas separation composite membrane, but also significantly improves the hydrophilicity of the gas separation membrane, so that the prepared hydrophilic modified composite gas separation membrane still maintains a high gas permeation rate.
[0050] Furthermore, compared to traditional hydrophilic modification techniques, the method for preparing the hydrophilic modified composite gas separation membrane provided by this invention utilizes interfacial polymerization to achieve hydrophilic modification of the hydrophobic polymer layer. This preparation method features simple equipment, easy operation, good technical and economic efficiency, and ease of industrial application.
[0051] According to the present invention, the concentration of polyacrylamide chloride in the organic phase is 0.025-0.3 wt%.
[0052] Furthermore, the concentration of polyacrylamide chloride in the organic phase is 0.05-0.20 wt%.
[0053] According to the present invention, the polyacryl chloride is selected from at least one of oxaloyl chloride, adipicoyl chloride, cyclohexanoyl chloride, terephthaloyl chloride, isophthaloyl chloride and trimesoyl chloride, preferably selected from isophthaloyl chloride and / or trimesoyl chloride.
[0054] In this invention, there is no particular limitation on the volume ratio of the organic phase to the area of the composite membrane, which can be adjusted according to actual process conditions. For example, the volume ratio of the organic phase to the area of the composite membrane can be 0.1-3 mL / cm². 2 Preferably, it is 0.2-1.5 mL / cm 2 .
[0055] In this invention, there is no particular limitation on the type of organic solvent in the organic phase. It can be a conventional type of organic solvent in the art, such as n-hexane, cyclohexane, cyclopentane, n-heptane, isoparaffins Isopar E, Isopar G, etc. Preferably, considering the volatility and universality of the solvent, the organic solvent is selected from n-hexane and / or n-heptane.
[0056] According to the present invention, the concentration of the polyamine containing ether bonds in the aqueous phase is 0.02-1 wt%, the concentration of the hydroxyl-containing compound is 0-0.1 wt%, the concentration of the acid absorbent is 0.1-1 wt%, and the concentration of the surfactant is 0-0.3 wt%.
[0057] Further, the concentration of the polyamine containing ether bonds in the aqueous phase is selected to be 0.08-0.3 wt%, the concentration of the hydroxyl-containing compound is 0.02-0.08 wt%, the concentration of the acid absorbent is 0.3-0.9 wt%, and the concentration of the surfactant is 0.05-0.2 wt%.
[0058] According to the present invention, the polyamine containing the ether bond is selected from at least one of polyoxyethylene diamine, ethylene glycol bis(3-aminopropyl) ether, polyetheramine and diethylene glycol bis(3-aminopropyl) ether.
[0059] According to the present invention, the hydroxyl-containing compound is selected from at least one of polyvinyl alcohol, (2-hydroxypropyl)-α-cyclodextrin, (2-hydroxypropyl)-β-cyclodextrin and water-soluble polymeric cyclodextrin.
[0060] In a preferred embodiment of the present invention, the hydroxyl-containing compound is selected from at least one of (2-hydroxypropyl)-α-cyclodextrin, (2-hydroxypropyl)-β-cyclodextrin, and water-soluble polymeric cyclodextrin.
[0061] In this invention, the use of the aforementioned specific type of hydroxyl-containing compound enables the hydrophilic polymer layer in the hydrophilic modified composite gas separation membrane to contain a 3D cavity structure, which can further reduce the resistance to gas transmission and further improve the gas permeation rate of the hydrophilic modified composite gas separation membrane.
[0062] In one specific embodiment of the present invention, the hydroxyl-containing compound is (2-hydroxypropyl)-β-cyclodextrin.
[0063] According to the present invention, the acid absorbent is selected from at least one of triethylamine, sodium hydroxide, sodium bicarbonate and sodium carbonate.
[0064] In a preferred embodiment of the present invention, the acid absorbent is selected from triethylamine and / or sodium carbonate.
[0065] According to the present invention, the surfactant is a nonionic surfactant.
[0066] In this invention, when a nonionic surfactant is used, it has a smaller effect on the ions of monomers in the aqueous phase, so that the monomers in the aqueous phase maintain good activity and reactivity, which is more conducive to regulating the interfacial polymerization reaction.
[0067] Furthermore, the surfactant is selected from at least one of Tween, polyoxyethylene ether, and polyethylene glycol, preferably polyethylene glycol.
[0068] In this invention, there is no particular limitation on the type of solvent in the aqueous phase; for example, it can be water.
[0069] According to the present invention, the duration of the first contact is 10-180 s, preferably 30-120 s.
[0070] According to the present invention, the drying temperature is 10-50°C, preferably 25-35°C.
[0071] In this invention, there are no particular limitations on the drying method, such as forced air drying.
[0072] According to the present invention, the conditions for the second contact include: a contact time of 10-300 s and a contact temperature of 15-50 °C.
[0073] In this invention, by controlling the conditions of the second contact to meet the above-mentioned range, it is possible for polyacrylamide chlorides, polyamines containing ether bonds, and optionally hydroxyl-containing compounds to undergo interfacial polymerization reactions on the surface of the composite film to form a hydrophilic polymer layer.
[0074] Furthermore, the conditions for the second contact include: a contact time of 60-180 seconds and a contact temperature of 20-40°C.
[0075] According to the present invention, the heat treatment conditions include: a heat treatment temperature of 45-80°C and a heat treatment time of 0-15 min.
[0076] Furthermore, the heat treatment conditions include: a heat treatment temperature of 50-65℃ and a heat treatment time of 5-10 min.
[0077] According to the present invention, the method further includes washing the product after the second contact in step (2).
[0078] In this invention, the product after the second contact in step (2) is pre-washed and then heat-treated to remove unreacted monomers, so that the hydrophilic modified composite gas separation membrane maintains high gas permeability.
[0079] According to the present invention, the detergent for washing is selected from water and / or alcohol.
[0080] Furthermore, when the detergent is a mixture of water and alcohol, the volume ratio of water to alcohol is 1:0.5-10, preferably 1:1-5.
[0081] In this invention, there is no particular limitation on the type of alcohol, and it can be any alcohol commonly used in the art, such as methanol and / or ethanol.
[0082] According to the present invention, the washing is repeated 0-5 times, preferably 1-3 times.
[0083] In this invention, there are no particular limitations on the method for preparing the hydrophobic polymer layer on the porous support layer; conventional methods in the art can be used.
[0084] In a preferred embodiment of the present invention, the method for preparing a hydrophobic polymer layer on a porous support layer includes:
[0085] The composite membrane is obtained by coating a hydrophobic polymer solution onto a porous support layer and then drying it.
[0086] According to the present invention, the concentration of the hydrophobic polymer solution is 0.01-0.5 wt%.
[0087] In this invention, when the concentration of the hydrophobic polymer solution is controlled to meet the above-mentioned range, the coating is performed at a lower concentration of the hydrophobic polymer solution, which can avoid the adverse reduction of the gas permeability of the gas separation membrane due to the excessive thickness of the hydrophobic polymer layer.
[0088] Furthermore, the concentration of the hydrophobic polymer solution is 0.02-0.2 wt%.
[0089] In this invention, there are no particular requirements for the volume ratio of the hydrophobic polymer solution to the area of the porous support layer, which can be adjusted according to actual process conditions. For example, the volume ratio of the hydrophobic polymer solution to the area of the porous support layer is 0.001-1 mL / cm². 2 Preferably, it is 0.005-0.5 mL / cm 2 .
[0090] According to the present invention, the hydrophobic polymer is selected from at least one of poly(1-trimethylsilyl-1-propyne), polydimethylsiloxane, and polydimethylsiloxane-polyoxyethylene copolymer.
[0091] In this invention, there are no particular limitations on the drying conditions after coating the porous support layer with the hydrophobic polymer solution; conventional drying conditions in the art are sufficient.
[0092] In one specific embodiment of the present invention, the hydrophilic modified composite gas separation membrane is prepared according to the following method:
[0093] (i) The composite membrane is obtained by coating a hydrophobic polymer solution onto a porous support layer and then drying it;
[0094] (ii) After the composite membrane is first contacted with an organic phase containing polyacryl chloride and dried, it is then second contacted with an aqueous phase containing a polyamine containing an ether bond, optionally a hydroxyl compound, an acid absorbent and optionally a surfactant, and then subjected to heat treatment to obtain the hydrophilic modified composite gas separation membrane.
[0095] A third aspect of the present invention provides a hydrophilic modified composite gas separation membrane prepared by the above method.
[0096] The fourth aspect of the present invention provides an application of the above-mentioned hydrophilic modified composite gas separation membrane in the separation or purification of gas mixtures.
[0097] In this invention, the hydrophilic composite gas separation membrane is preferably suitable for the purification of nitrogen, oxygen, and carbon dioxide, and is also suitable for the separation of gas mixtures, including but not limited to the separation of two or more mixed gases from nitrogen, oxygen, carbon dioxide, sulfur dioxide, methane, ethylene, propylene, ethanol, propanol, butanol, and water vapor.
[0098] The present invention will be described in detail below through embodiments.
[0099] (1) Gas separation performance test: Important performance indicators for evaluating gas separation membranes include permeability coefficient (P), permeation rate (R), and separation coefficient (α). The unit of gas permeability coefficient is Barrer (1 Barrer = 10⁻⁶). -10 cm 3 (STP)cm / (cm 2Gas permeation rate (g / cmHg) indicates the ease with which a gas permeates through the membrane, characterizing the membrane material's gas permeation capacity. For flat-sheet composite membranes, considering the influence of functional layer thickness, the gas permeation rate is typically used to evaluate the membrane's permeation performance. The unit of gas permeation rate is GPU (1 GPU = 10⁻⁶). -6 cm 3 (STP) / (cm 2 The permeation rate (·s·cmHg) is used to characterize the gas permeation capacity during membrane applications. The separation coefficient α is the ratio of the permeation rates of two gases in the membrane; α is dimensionless and used to characterize the selective permeation capacity of gas components in the membrane.
[0100] (2) Contact Angle Test: The contact angle is an important indicator for evaluating the hydrophilicity or hydrophobicity of the membrane surface. Typically, a tangent is drawn along the gas-liquid interface at the gas-liquid-solid three-phase contact point; the angle between this tangent and the liquid-solid interface is defined as the contact angle. Generally, a contact angle greater than 90° indicates hydrophobic properties, while a contact angle less than 90° indicates hydrophilic properties. The contact angle data below were measured using a German KRUSS contact angle measuring instrument.
[0101] (3) Characterization of membrane physical and chemical structure: Compared with unmodified PDMS, the hydrophilic modified composite gas separation membrane containing a hydrophilic polymer layer has nitrogen elements and corresponding functional groups of polyamide on its surface, and the membrane thickness also increases. To verify the changes in the chemical structure of the membrane before and after the interface modification, the chemical structure of the membrane samples was characterized using an attenuated total reflectance Fourier transform infrared spectroscopy (ATR-FTIR) and an X-ray photoelectron spectroscopy (XPS) instrument from Thermo Scientific, USA. In addition, the surface and cross-sectional structure of the membrane were characterized using a scanning electron microscope (SEM) from Hitachi, Japan, and the thickness of each layer of the composite membrane was measured.
[0102] The raw materials used in the examples and comparative examples were all commercially available products.
[0103] Example 1
[0104] S1, In the polysulfone porous support layer (thickness 50μm, area 180cm²) 2 A 90 mL solution of a 0.035 wt% hydrophobic polymer PDMS was coated onto the surface, and the composite film was obtained after drying.
[0105] S2. Prepare an organic phase solution containing 0.10 wt% trimesoyl chloride, with n-heptane as the organic solvent;
[0106] S3. Prepare an aqueous solution containing 0.05 wt% diethylene glycol bis(3-aminopropyl) ether, 0.05 wt% (2-hydroxypropyl)-β-cyclodextrin, 0.40 wt% sodium carbonate, and 0.05 wt% polyethylene glycol using deionized water;
[0107] S4. After the composite membrane is first contacted with 90 mL of the organic phase solution from step S2 for 60 s, it is then dried by blowing air at 30 °C. After that, it is contacted with 90 mL of the aqueous phase solution from step S3 at 30 °C for 120 s, then washed three times with deionized water. The washed composite membrane is then heat-treated at 55 °C for 10 min and dried to obtain the hydrophilic modified composite gas separation membrane A1.
[0108] The surface structure (left) and cross-sectional structure (right) of the hydrophilic modified composite gas separation membrane A1 are shown in the figure. Figure 1 As shown in the cross-sectional diagram, there is no obvious boundary between the interfacial polymerization modified layer and the PDMS layer, indicating good bonding between the two layers. Table 1 shows that the membrane surface contains nitrogen elements with amide bonds, and the membrane surface contact angle exhibits hydrophilic properties.
[0109] The infrared spectrum of the hydrophilic modified composite gas separation membrane A1 is as follows: Figure 2 As shown, from Figure 2 It can be seen that characteristic peaks of amide and ester groups appeared after interfacial polymerization modification. The XPS spectrum of the hydrophilic modified composite gas separation membrane A1 is as follows: Figure 3 As shown, the characteristic peak of N element indicates that a hydrophilic polymer layer containing amide bonds was successfully generated after the interfacial polymerization reaction, and the weak characteristic peak of Si indicates that some silane segments are embedded in the hydrophilic polymer layer, indicating that the hydrophilic polymer layer and the hydrophobic polymer layer (PDMS layer) have good compatibility.
[0110] Example 2
[0111] S1, In the polysulfone porous support layer (thickness 50μm, area 180cm²) 2 A 90 mL solution of a 0.08 wt% hydrophobic polymer PTMSP is coated onto the surface, and after drying, a hydrophobic polymer layer is formed.
[0112] S2. Prepare an organic phase solution containing 0.025 wt% adipicoyl chloride, with cyclohexane as the organic solvent.
[0113] S3. Prepare an aqueous solution containing 1 wt% polyetheramine, 0.02 wt% polyvinyl alcohol, 0.30 wt% sodium hydroxide, and 0.20 wt% Tween using deionized water.
[0114] S4. After the composite membrane is first contacted with 90 mL of the organic phase solution from step S2 for 30 s, it is then dried by blowing air at 20 °C. After that, it is contacted with 90 mL of the aqueous phase solution from step S3 at 20 °C for 60 s. Then, it is first washed twice with deionized water and then once with ethanol. The washed composite membrane is then heat-treated at 50 °C for 15 min and dried to obtain the hydrophilic modified composite gas separation membrane A2.
[0115] Example 3
[0116] S1, In the polysulfone porous support layer (thickness 50μm, area 180cm²) 2 A 90 mL solution of 0.50 wt% PDMS-PEO polymer was coated onto the surface, and after drying, a hydrophobic polymer layer was formed.
[0117] S2. Prepare an organic phase solution containing 0.30 wt% isophthaloyl chloride, with n-hexane as the organic solvent.
[0118] S3. Prepare an aqueous solution containing 0.10 wt% polyoxyethylene diamine, 0.10 wt% polyvinyl alcohol, 0.10 wt% triethylamine, and 0.3 wt% polyoxyethylene ether using deionized water.
[0119] S4. After the composite membrane is first contacted with 90 mL of the organic phase solution from step S2 for 120 s, it is then dried by blowing air at 35 °C. After that, it is contacted with 90 mL of the aqueous phase solution from step S3 at 40 °C for 180 s. Then, it is washed once with a mixture of deionized water and ethanol, wherein the volume ratio of deionized water to ethanol is 1:1. The washed composite membrane is then heat-treated at 60 °C for 5 min and dried to obtain the hydrophilic modified composite gas separation membrane A3.
[0120] Example 4
[0121] S1 is the same as S1 in Example 1.
[0122] S2 is the same as S2 in Example 1.
[0123] S3. Prepare an aqueous solution containing 0.10 wt% diethylene glycol bis(3-aminopropyl) ether, 0.025 wt% (2-hydroxypropyl)-α-cyclodextrin, 0.40 wt% sodium carbonate, and 0.05 wt% polyethylene glycol using deionized water.
[0124] S4. The washing method is as follows: first wash with ethanol once, then wash with deionized water once. Everything else is the same as S4 in Example 1. A hydrophilic modified composite gas separation membrane A4 is obtained.
[0125] Example 5
[0126] S1 is the same as S1 in Example 1.
[0127] S2 is the same as S2 in Example 1.
[0128] S3. Prepare an aqueous solution containing 0.08 wt% diethylene glycol bis(3-aminopropyl) ether, 0.075 wt% β-cyclodextrin, 0.40 wt% sodium carbonate, and 0.05 wt% polyethylene glycol using deionized water.
[0129] S4. The washing method is as follows: first wash twice with deionized water, then wash once with ethanol. Everything else is the same as S4 in Example 1. A hydrophilic modified composite gas separation membrane A5 is obtained.
[0130] Example 6
[0131] S1 is the same as S1 in Example 1.
[0132] S2 is the same as S2 in Example 1.
[0133] S3. Prepare an aqueous solution containing 0.05 wt% diethylene glycol bis(3-aminopropyl) ether, 0.05 wt% (2-hydroxypropyl)-β-cyclodextrin, 0.40 wt% sodium carbonate, and 0.05 wt% sodium dodecyl sulfate using deionized water.
[0134] S4 is the same as S4 in Example 1. A hydrophilic modified composite gas separation membrane A6 is obtained.
[0135] Example 7
[0136] S1 is the same as S1 in Example 1.
[0137] S2 is the same as S2 in Example 1.
[0138] S3. Prepare an aqueous solution containing 0.05 wt% diethylene glycol bis(3-aminopropyl) ether, 0.40 wt% sodium carbonate, and 0.05 wt% polyethylene glycol using deionized water.
[0139] S4 is the same as S4 in Example 1. A hydrophilic modified composite gas separation membrane A7 is obtained.
[0140] Example 8
[0141] S1 is the same as S1 in Example 1.
[0142] S2 is the same as S2 in Example 1.
[0143] S3, Step (3): Prepare an aqueous solution containing 0.05 wt% diethylene glycol bis(3-aminopropyl) ether, 0.05 wt% (2-hydroxypropyl)-β-cyclodextrin, and 0.40 wt% sodium carbonate using deionized water;
[0144] S4 is the same as S4 in Example 1. A hydrophilic modified composite gas separation membrane A8 is obtained.
[0145] Example 9
[0146] S1 is the same as S1 in Example 1.
[0147] S2 is the same as S2 in Example 1.
[0148] S3 is the same as S3 in Example 1.
[0149] S4, without washing, is the same as S4 in Example 1. A hydrophilic modified composite gas separation membrane A9 is obtained.
[0150] Comparative Example 1
[0151] A gas composite separation membrane was prepared according to the method of Example 1, except that only step S1 was performed. Gas composite separation membrane D1 was obtained.
[0152] The infrared spectrum and XPS spectrum of the composite gas separation membrane D1 are as follows: Figure 2 and Figure 3 As shown, by Figure 2 and Figure 3 It can be seen that the surface of the gas composite separation membrane D1 does not contain the characteristic peak of N element, indicating that it does not contain the characteristic peak of amide group, but has obvious characteristic peak of silane chain segment.
[0153] Comparative Example 2
[0154] The gas composite separation membrane was prepared according to the method of Example 1, with the following difference:
[0155] In step S2, 0.05 wt% polyethylene polyamine is used instead of 0.05 wt% diethylene glycol bis(3-aminopropyl) ether. Gas composite separation membrane D2 is then prepared.
[0156] Comparative Example 3
[0157] A gas composite separation membrane was prepared according to the method of Example 1, except that after step S1, the dried composite membrane was treated with plasma technology for 30 seconds, and steps S2-S4 were omitted, resulting in gas composite separation membrane D3. The gas used for plasma treatment was air, with a pressure of 1000 mTorr (133 Pa) and a processing power of 200 W.
[0158] The surface contact angle, surface contact angle after being placed in room temperature air for one month, thickness of each layer, and content of each atom on the membrane surface of the gas composite separation membranes prepared in the examples and comparative examples were tested, and the results are shown in Table 1.
[0159] Table 1
[0160]
[0161]
[0162] a - Relative atomic content from XPS surface analysis results.
[0163] As shown in Table 1, after interfacial polymerization modification, the hydrophilicity of the membrane surface increased, the Si content decreased, and N element was present, indicating the formation of amide segments in the modified layer of the separation membrane surface. Furthermore, a certain amount of Si element remained on the membrane surface after interfacial polymerization modification, which can be attributed to the swelling of PDMS segments in the organic phase during the interfacial polymerization process. The embedding of PDMS segments in the interfacial polymerization modified layer indicates excellent interlayer bonding between the interfacial polymerization layer and the PDMS layer.
[0164] Specifically, compared to Example 1, Example 7, due to the absence of hydroxyl-containing compounds, resulted in a higher N atom content and lower O and Si atom content in the hydrophilic polymer layer of the gas composite separation membrane, leading to an increased thickness of the hydrophilic polymer layer. Notably, after one month, the hydrophilicity of the membrane surface treated with interfacial polymerization hydrophilic modification technology did not change significantly. However, the hydrophobicity of the membrane surface treated with plasma increased significantly, consistent with phenomena reported in the literature.
[0165] The gas permeation performance of the gas composite separation membranes prepared in the examples and comparative examples was tested, and the results are shown in Table 2.
[0166] Table 2
[0167]
[0168]
[0169] As can be seen from the results in Tables 1 and 2, compared with Comparative Examples 1-3, Examples 1-9 have increased surface hydrophilicity after modification because the interface modification layer contains unreacted amino, hydroxyl and amide structures. By introducing organic amine monomers containing flexible ether oxygen segments, the polymer chain stacking allows the modified membrane to still maintain good gas permeability.
[0170] In Examples 1 and 4 of the present invention, cyclodextrin containing 3D cavities was introduced into the interfacial polymerization modification layer, which not only achieved hydrophilic modification but also maintained good gas permeability of the membrane.
[0171] The preferred embodiments of the present invention have been described in detail above; however, the present invention is not limited thereto. Within the scope of the inventive concept, various simple modifications can be made to the technical solutions of the present invention, including combinations of various technical features in any other suitable manner. These simple modifications and combinations should also be considered as the content disclosed in the present invention and are all within the protection scope of the present invention.
Claims
1. A hydrophilic modified composite gas separation membrane, characterized in that, The gas separation membrane comprises, in sequence, a porous support layer, a hydrophobic polymer layer, and a hydrophilic polymer layer; The hydrophilic polymer forming the hydrophilic polymer layer includes structural unit I from polyacrylamide chloride, structural unit II from polyamine containing ether bonds, and optionally structural unit III from hydroxyl-containing compounds; In this structure, structural unit I and structural unit II are connected by amide bonds, and structural unit I and structural unit III are connected by ester groups.
2. The hydrophilic modified composite gas separation membrane according to claim 1, wherein, The polyacryl chloride is selected from at least one of oxaloyl chloride, adipicoyl chloride, cyclohexyl chloride, terephthaloyl chloride, isophthaloyl chloride and trimesoyl chloride, preferably selected from isophthaloyl chloride and / or trimesoyl chloride; Preferably, the polyamine containing ether bonds is selected from at least one of polyoxyethylene diamine, ethylene glycol bis(3-aminopropyl) ether, polyetheramine, and diethylene glycol bis(3-aminopropyl) ether; Preferably, the hydroxyl-containing compound is selected from at least one of polyvinyl alcohol, (2-hydroxypropyl)-α-cyclodextrin, (2-hydroxypropyl)-β-cyclodextrin and water-soluble polymeric cyclodextrin, and more preferably from at least one of (2-hydroxypropyl)-α-cyclodextrin, (2-hydroxypropyl)-β-cyclodextrin and water-soluble polymeric cyclodextrin.
3. The hydrophilic modified composite gas separation membrane according to claim 1 or 2, wherein, The polymer forming the hydrophobic polymer layer is selected from at least one of poly(1-trimethsilyl-1-propyne), polydimethylsiloxane, and polydimethylsiloxane-polyoxyethylene copolymer.
4. The hydrophilic modified composite gas separation membrane according to any one of claims 1-3, wherein, The contact angle of the gas separation membrane is 50-85°, preferably 65-80°.
5. The hydrophilic modified composite gas separation membrane according to any one of claims 1-4, wherein, The thickness of the hydrophobic polymer layer is 50-300 nm, preferably 80-150 nm; Preferably, the thickness of the hydrophilic polymer layer is 50-500 nm, and more preferably 90-200 nm.
6. A method for preparing a hydrophilically modified composite gas separation membrane, characterized in that, The method includes: (1) A hydrophobic polymer layer is prepared on a porous support layer to obtain a composite membrane; (2) After the composite membrane is first contacted with an organic phase containing polyacryl chloride and dried, it is then second contacted with an aqueous phase containing a polyamine containing an ether bond, optionally a hydroxyl compound, an acid absorbent and optionally a surfactant, and optionally subjected to heat treatment to obtain the hydrophilic modified composite gas separation membrane.
7. The method according to claim 6, wherein, The concentration of polyacryl chloride in the organic phase is 0.025-0.3 wt%, preferably 0.05-0.2 wt%. Preferably, the polyacryl chloride is selected from at least one of oxaloyl chloride, adipicoyl chloride, cycloadipic chloride, terephthaloyl chloride, isophthaloyl chloride and trimesoyl chloride, and more preferably from isophthaloyl chloride and / or trimesoyl chloride.
8. The method according to claim 6 or 7, wherein, The concentration of the polyamine containing ether bonds in the aqueous phase is 0.02wt%-1wt%, preferably 0.08-0.3wt%, the concentration of the hydroxyl-containing compound is 0-0.1wt%, preferably 0.02-0.08wt%, the concentration of the acid absorbent is 0.1-1wt%, preferably 0.3-0.9wt%, and the concentration of the surfactant is 0-0.3wt%, preferably 0.05-0.2wt%. Preferably, the polyamine containing ether bonds is selected from at least one of polyoxyethylene diamine, ethylene glycol bis(3-aminopropyl) ether, polyetheramine, and diethylene glycol bis(3-aminopropyl) ether; Preferably, the hydroxyl-containing compound is selected from at least one of polyvinyl alcohol, (2-hydroxypropyl)-α-cyclodextrin, (2-hydroxypropyl)-β-cyclodextrin and water-soluble polymeric cyclodextrin, and more preferably from at least one of (2-hydroxypropyl)-α-cyclodextrin, (2-hydroxypropyl)-β-cyclodextrin and water-soluble polymeric cyclodextrin; Preferably, the acid absorbent is selected from at least one of triethylamine, sodium hydroxide, sodium bicarbonate, and sodium carbonate; Preferably, the surfactant is a nonionic surfactant, and is preferably selected from at least one of Tween, polyoxyethylene ether, and polyethylene glycol.
9. The method according to any one of claims 6-8, wherein, The duration of the first contact is 10-180 seconds; Preferably, the drying temperature is 10-50°C; Preferably, the conditions for the second contact include: a contact time of 10-300 seconds and a contact temperature of 15-50°C; Preferably, the heat treatment conditions include: a heat treatment temperature of 45-80℃ and a heat treatment time of 0-15min.
10. The method according to any one of claims 6-9, wherein, The method further includes: The product after the second contact in step (2) is washed; Preferably, the detergent for washing is selected from water and / or alcohol; Preferably, the washing is repeated 0-5 times, and more preferably 1-3 times.
11. The method according to any one of claims 6-10, wherein, Methods for preparing hydrophobic polymer layers on porous support layers include: The composite membrane is obtained by coating a hydrophobic polymer solution onto a porous support layer and then drying it. Preferably, the concentration of the hydrophobic polymer solution is 0.01-0.5 wt%. Preferably, the hydrophobic polymer is selected from at least one of poly(1-trimethylsilyl-1-propyne), polydimethylsiloxane, and polydimethylsiloxane-polyoxyethylene copolymer.
12. A hydrophilic modified composite gas separation membrane prepared by the method according to any one of claims 6-11.
13. The application of the hydrophilic modified composite gas separation membrane according to any one of claims 1-5 and 12 in the separation of gas mixtures.
Citation Information
Patent Citations
Polyether block polyamide / polydimethylsiloxane composite gas separation membrane, preparation method and application
CN115608177A
